PERANCANGAN MESIN PENATA PRODUK OTOMATIS DENGAN MEKANISME CNC 3-axis BERBASIS ARDUINO GRBL - Azam Milah Muhamad; Yudha Dewangga; Risat Dwi Yulianto; Al Maida Nurul Alaika; Faiq Akmal; Dhiya Luqyana (Program Studi Pendidikan Teknik Mesin, Fakultas Keguruan dan Ilmu Pendidikan, Universitas Palangka Raya, 2026)
This research aims to design an automatic product arranging machine based on a 3-axis CNC mechanism controlled by Arduino GRBL to improve the efficiency of the final stage of manufacturing, particularly in the arrangement of lightweight cardboard packaging. The Quality Function Deployment (QFD) method was applied to translate five main consumer requirements high accuracy, transfer speed, product size flexibility, operational simplicity, and cost-effectiveness into technical specifications. Three design alternatives were evaluated through Concept Screening and Scoring, resulting in the selection of Design Alternative 3, which is modular and easy to maintain. Technical analysis demonstrated adequate performance, with a load force of 0.00735 [N], motor torque of 0.000294 [Nm], movement speed of 0.0333 [m/s], motor power of 0.0037 [W], and frame deflection of 2.55 × 10⁻⁸ [mm]. These values indicate that the system ensures stability, energy efficiency, and precision in operation. The use of 6061 aluminum alloy for the frame and NEMA 17 stepper motors with A4988 drivers guarantees rigidity, accuracy, and production cost efficiency. The novelty of this research lies in adapting the 3-axis CNC system to handle non-electronic objects (40×40×40 mm, 20 grams cardboard boxes), extending its application beyond previous studies that focused on small SMD components. In the future, this research will focus on developing advanced control systems and sensors to enhance accuracy, speed, and the diversity of object shapes that can be manipulated.